RESPRESENTATIONS OF MASCULINITY IN BARBIE FILM 2023 - Ramdhan, Mochamad Akmal; Yatmikasari, Ika; Sudarisman, Yoga (Saksama: Jurnal Sastra, 2024)
Masculinity is the characteristics that are traditionally thought to be typical of or suitable for men. This research attempts to discuss a character's masculinity in The Barbie 2023 Film. To specify the research, the researcher divided this analysis into two research questions, they are: 1) What are the elements of masculinity depicted in The 2023 Barbie Film? 2) How is the depiction of stereotypical masculinity in The 2023 Barbie Film? Masculinity in Barbie 2023 is very interesting to discuss because it can be identified from various elements contained in the film, in this case the identification of masculinity can be seen from how the characters in this film behave, the instrinsic elements implied in the film, the setting, and also other things that illustrate how the elements of masculinity are contained in the film. The results of this study found two findings, namely the first is what elements of masculinity are found in this film in the form of how the character Ken has an athletic posture that strongly shows elements of masculinity and in several scenes in the film shows masculinity, then the findings of other stereotypes of masculinity that the author managed to identify from the dialog, character acting, setting, or atmosphere that is contained in this film.